Long and Accurate: How HiFi Sequencing is Transforming Genomics - Wang (王博), Bo; Jia (贾鹏), Peng; Gao (高胜寒), Shenghan; Zhao (赵焕焕), Huanhuan; Zheng (郑高洋), Gaoyang; Xu (许林峰), Linfeng; Ye (叶凯), Kai (Genomics, proteomics & bioinformatics, 2025)
Recent developments in PacBio high-fidelity (HiFi) sequencing technologies have transformed genomic research, with circular consensus sequencing now achieving 99.9% accuracy for long (up to 25 kb) single-molecule reads. This method circumvents biases intrinsic to amplification-based approaches, enabling thorough analysis of complex genomic regions [including tandem repeats, segmental duplications, ribosomal DNA (rDNA) arrays, and centromeres] as well as direct detection of base modifications, furnishing both sequence and epigenetic data concurrently. This has streamlined a number of tasks including genome assembly, variant detection, and full-length transcript analysis. This review provides a comprehensive overview of the applications and challenges of HiFi sequencing across various fields, including genomics, transcriptomics, and epigenetics. By delineating the evolving landscape of HiFi sequencing in multi-omics research, we highlight its potential to deepen our understanding of genetic mechanisms and to advance precision medicine.